BRANDING dan OPTIMALISASI TEKNOLOGI INFORMASI UMKM UNTUK MENINGKATKAN PENJUALAN PRODUK KUE CUHCUR TEH OPI SEBAGAI PRODUK UNGGULAN UMKM DESA SUKABAKTI TAROGONG KIDUL KABUPATEN GARUT - Tri Utami, Alia; Irhamuddin, Muhammad; Nurhayati, Risti; Mery Lestari, Jesica; Darmawan, Indra; Rohanah, Een; Sri Agustina, Istiqomah; Iskandar, Yogi; Nur Anggraila, Auriela; Raina, Rinda; Zaldy Ardiansyah, Muchamad (ABISATYA DINAMIKA ISWARA PUBLISHING, 2024)
The development of micro, small, and medium enterprises (MSMEs), especially in villages, is very important to encourage economic growth both at the village and national levels. The development of a business is closely related to the marketing strategy, one of which is through branding. Branding is a promotional activity aimed at establishing a brand and its attributes so that MSME products can be more widely recognized and increase their sales.In addition, the utilization of digital technology through the optimization of information technology and e-commerce is also key to expanding market reach and enhancing competitiveness.Kue Cuhcur The Opi is one of the small and medium enterprises with flagship products located in Sukabakti Village. The KKN Group 60 of Universitas Muhammadiyah Bandung is developing a business through branding and optimization of information technology. In collaboration with Dinas Koperasi dan UMKM of Garut City, the KKn Team carried out various marketing activities that assist the MSMEs of Sukabakti Village, particularly Keuh Cuhcur Teh Opi. These activities were conducted based on a needs analysis performed on The Opi Cucur Cake MSME, including product branding (logo and packaging design), registration of a Shopee account, creation of a location point on Google Maps, and the establishment of a Business Identification Number (NIB) to ensure that Kue Cuhcur The Opi business is legally protected. The aim of this development effort through branding is to improve business management by enhancing marketing strategies and expanding product exposure through digital mediums. The method used is data collection through interviews and direct observation. The results of this community service activity are the creation of a more attractive new logo, ownership of a Business Identification Number (NIB), registration of a Shopee account, and the business location marked on Google Maps.